Protease-activated receptor 1 is implicated in irritable bowel syndrome mediators–induced signaling to thoracic human sensory neurons. Issue 7 (July 2018) - Desormeaux, Cleo; Bautzova, Tereza; Garcia-Caraballo, Sonia; Rolland, Corinne; Barbaro, Maria Raffaella; Brierley, Stuart M.; Barbara, Giovanni; Vergnolle, Nathalie; Cenac, Nicolas
Abstract : Abstract: Proteases and protease-activated receptors (PARs) are major mediators involved in irritable bowel syndrome (IBS). Our objectives were to decipher the expression and functionality (calcium signaling) of PARs in human dorsal root ganglia (DRG) neurons and to define mechanisms involved in human sensory neuron signaling by IBS patient mediators. Human thoracic DRG were obtained from the national disease resource interchange. Expression of PAR1, PAR2, and PAR4 was assessed by immunohistochemistry and quantitative reverse transcription PCR (RT-qPCR) in whole DRG or in primary cultures of isolated neurons. Calcium signaling in response to PAR agonist peptides (PAR-AP), their inactive peptides (PAR-IP), thrombin (10 U/mL), supernatants from colonic biopsies of patients with IBS, or healthy controls, with or without PAR1 or PAR4 antagonist were studied in cultured human DRG neurons. PAR1, PAR2, and PAR4 were all expressed in human DRG, respectively, in 20%, 40%, and 40% of the sensory neurons. PAR1 -AP increased intracellular calcium concentration in a dose-dependent manner. This increase was inhibited by PAR1 antagonism. By contrast, PAR2 -AP, PAR4 -AP, and PAR-IP did not cause calcium mobilization. PAR1 -AP–induced calcium flux was significantly reduced by preincubation with PAR4 -AP, but not with PAR2 -AP. Thrombin increased calcium flux, which was inhibited by a PAR1 antagonist and increased by a PAR4 antagonist. Supernatants from colonic biopsies of patients with IBS induced calcium flux in human sensory neurons compared with healthy controls, and this induction was reversed by a PAR1 antagonist. Taken together, our results highlight that PAR1 antagonism should be investigated as a new therapeutic target for IBS symptoms. Abstract : Supplemental Digital Content is Available in the Text.PAR1 is expressed and functional in human primary afferents, where it mediates calcium signal induced by irritable bowel syndrome patient tissue mediators.